Understanding growth mechanisms and tribocorrosion behaviour of porous TiO2 anodic films containing calcium, phosphorous and magnesium - Oliveira, Fernando Gabriel [UNESP]; Ribeiro, Ana Lúcia Roselino [UNESP]; Perez, Geronimo; Archanjo, Braulio Soares; Gouvea, Cristol de Paiva; Araujo, Joyce Rodrigues de; Campos, Andrea Porto Carreiro; Kuznetsov, Alexei; Almeida, Clara Muniz da Silva de; Maru, Marcia Marie; Achete, Carlos Alberto; Ponthiaux, Pierre; et al. (Elsevier B.V., 2015)
The growth of the dental implant market increases the concern regarding the quality, efficiency, and lifetime of dental implants. Titanium and its alloys are dominant materials in this field thanks to their high biocompatibility and corrosion resistance, but they possess a very low wear resistance. Besides problems related to osteointegration and bacterial infections, tribocorrosion phenomena being the simultaneous action between corrosion and wear, are likely to occur during the lifetime of the implant. Therefore, tribocorrosion resistant surfaces are needed to guarantee the preservation of dental implants.This work focused on the incorporation of magnesium, together with calcium and phosphorous, in the structure of titanium oxide films produced by micro- arc oxidation (MAO). The characterization ofmorphology, chemical composition, and crystalline structure of the surfaces provided important insights leading to (1) a better understanding of the oxide film growth mechanisms during the MAO treatment; and (2) a better awareness on the degradation process during tribocorrosion tests. The addition of magnesium was shown to support the formation of rutile which improves the tribocorrosion properties ofthe surfaces.
Keywords: Titanium; Surface modification; Micro-arc oxidation; Dental implant; Tribocorrosion